Relationship between electrical conduction and phasic left atrial function: P-wave signal-averaged electrocardiography and time-left atrial volume curve assessments using two-dimensional speckle-tracking echocardiography - Tanaka, Shinichiro; Noda, Toshiyuki; Kawasaki, Masanori; Segawa, Tomonori; Tsugita, Natsumi; Fuseya, Takahiro; Kubota, Tomoki; Iwama, Makoto; Nishigaki, Kazuhiko; Watanabe, Sachiro; Minagawa, Taro; Ohashi, Hiroshige; et al. (Heart and Vessels, 2019)
P-wave signal-averaged electrocardiography (P-SAECG) can detect imperceptible conduction abnormalities, and volume analysis using two-dimensional speckle-tracking echocardiography (2-DSTE) allows us to easily measure the phasic function of the left atrium (LA). Both conduction abnormalities and functional deformation of the LA may be linked to the clinical outcome; however, the exact relationship is unclear. The aim of this study was to investigate the relationship between the phasic function of the LA and electrical conduction using P-SAECG and 2-DSTE. The subjects were 112 male volunteers (age 46.9 ± 13.2 years) with normal cardiac function who underwent P-SAECG and 2-DSTE. The filtered p-wave duration (FPD) and the root-mean-square voltage for the last 20 ms (RMS20) on P-SAECG wave were measured in ms and μV, respectively. Total emptying function (EF) (reservoir function), passive EF (conduit function), and active EF (booster pump function) of the LA were calculated as percentages to evaluate phasic LA function using 2DSTE. The mean FPD was 134.3 ± 11.7 ms and the mean RMS20 was 4.59 ± 2.39 μV. The mean total EF was 60.5 ± 13.1%, mean passive EF was 39.4 ± 13.9%, and mean active EF was 35.1 ± 13.9%. FPD had a negative correlation with passive EF ( r = − 0.20, p = 0.039). FPD showed no significant relationship with total EF ( r = − 0.03, p = 0.78) or active EF ( r = 0.13, p = 0.18). There was a significant association between RMS20 and passive EF ( r = 0.19, p = 0.048); however, no there was no correlation between RMS20 and total EF ( r = 0.12, p = 0.23), or between RMS20 and passive EF ( r = − 0.02, p = 0.86). In multivariate regression analysis, passive EF was an independent factor that influenced FPD duration. This study indicated that FPD was associated with conduit function, which includes phasic LA function. Therefore, electrical conduction of the LA and left ventricular diastolic function are closely related. In the clinical setting, when conduction abnormalities are detected, lifestyle measures or interventions can be applied to reduce cardiovascular risk.